The Disguise of Cyber Crime in Illegal Investment Entities Post the Re-formulation of Law No. 11 of 2020 Concerning Job Creation in Indonesia - Edi Ribut Harwanto (Green Publisher Indonesia, 2024)
This research delves into cybercrime in the post-truth era, where falsehoods are often masked as truths. This phenomenon, known as